From Village to World: MSME Transformation Through Digital Platforms in Indonesia - Intan Juniarmi (Nomico, 2024)
This article discusses the transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the use of digital platforms. With increasing internet access and the use of information technology, MSMEs can expand their market reach from local to global scale. This study analyzes various strategies adopted by MSMEs to adapt to digitalization, as well as the challenges faced, such as limited resources and digital literacy. The results of the study show that MSMEs that successfully carry out digital transformation not only increase their competitiveness but also contribute to national economic growth. By utilizing e-commerce, social media, and other digital platforms, MSMEs are able to create innovations and strengthen social networks that support the sustainability of their businesses. This article is expected to provide insights for stakeholders in formulating policies that support the digital transformation of MSMEs in Indonesia.